Esophageal Mucosal Admittance: A New Technique to Diagnose Gastroesophageal Reflux Disease – Is It Feasible? - Dao HV; Hoang LB; Nguyen BP; Nguyen HL; Goldberg R; Allison J; Dao TMA; Matsumura T; Dao LV (Clinical and Experimental Gastroenterology, 2023)
Hang Viet Dao,1– 3 Long Bao Hoang,3 Binh Phuc Nguyen,3 Hoa Lan Nguyen,4 Robert Goldberg,4 Jeroan Allison,4 Thi Minh An Dao,5,6 Tomoaki Matsumura,7 Long Van Dao1,3 1Internal Medicine Faculty, Hanoi Medical University, Hanoi, Vietnam; 2Endoscopy Center, Hanoi Medical University Hospital, Hanoi, Vietnam; 3Institute of Gastroenterology and Hepatology, Hanoi, Vietnam; 4Department of Population and Quantitative Health Sciences, University of Massachusetts Medical School, Worcester, MA, USA; 5School of Public Health, University of Queensland, Brisbane, Australia; 6Epidemiology Department, Hanoi Medical University, Hanoi, Vietnam; 7Department of Gastroenterology, Graduate School of Medicine, Chiba University, Chiba, JapanCorrespondence: Hang Viet Dao, Institute of Gastroenterology and Hepatology, Floor 10, VCCI Tower, No. 9, Dao Duy Anh Street, Dong Da District, Hanoi City, 10000, Vietnam, Tel +84987988075, Email daoviethang@hmu.edu.vnPurpose: Esophageal mucosal admittance (MA) is a promising diagnostic method for gastroesophageal reflux disease (GERD). We conducted a study to describe the esophageal MA in patients with reflux symptoms and determine its diagnostic accuracy.Patients and Methods: We recruited 92 patients with ambulatory pH-impedance monitoring, upper gastrointestinal endoscopy, and MA measured by the tissue conductance meter. MA was measured during endoscopy at 5cm (distal esophagus) and 15cm above the Z line (middle esophagus), repeated at least five times at each position, and median MA was obtained. Afterwards, two biopsies were taken 5cm above the Z line for histopathological evaluation using the Esohisto criteria. Patients were classified as GERD or non-GERD according to the 2018 Lyon consensus.Results: The mean age was 43.2 years, and 42 patients were males. The most common symptoms were regurgitation (75.0%), belching (65.2%), and heartburn (46.7%). Twenty-three (32.3%) were diagnosed with GERD using the Lyon consensus, and 24 (26.1%) had esophagitis on histopathology. The median MA at the distal and middle esophagus was moderately correlated. The median MA at both positions was higher in the GERD group but only statistically significant in the middle esophagus. MA was not associated with pH-impedance parameters and esophagitis on histopathology. The diagnostic model developed using the logistic regression did not have good accuracy.Conclusion: MA was not different between GERD and non-GERD patients.Keywords: mucosal permeability, tissue conductance meter, pH-impedance monitoring, Lyon consensus